TYPICAL GRAY SOILS OF THE OLD IRRIGATED FERGANA REGION AND CULTI-VATION OF THE MALBORA VARIETY OF RASPBERRY (RUBUS IDEAEUS) (Scientific journal of the Fergana State University, 2026)
Among the agroecosystems of Uzbekistan, the Fergana Valley is of particular importance, its gray soils are distinguished by their high fertility. Studying the laws of biogeochemical cycling of elements in typical gray soils that were previously irrigated and determining their impact on plant development and crop quality is a relevant area of ​​modern scientific research, and one of the berries grown today is the cultivation of the “Malboro” raspberry variety.